Individual Differences in the Stability and Change of Childhood Depression: A Growth Mixture Model With Structured Residuals. Issue 4 (10th January 2021) - Hawrilenko, Matt; Masyn, Katherine E.; Cerutti, Janine; Dunn, Erin C.
Abstract : Studies of developmental trajectories of depression are important for understanding depression etiology. Existing studies have been limited by short time frames and no studies have explored a key factor: differential patterns of responding to life events. This article introduces a novel analytic technique, growth mixture modeling with structured residuals, to examine the course of youth depression in a large, prospective cohort ( N  = 11, 641, ages 4–16.5, 96% White). Age‐specific critical points were identified at ages 8 and 13 where depression symptoms spiked for a minority of children. Most depression risk was due to dynamic responses to environmental events, drawn not from a small pool of persistently depressed children, but a larger pool of children who varied across higher and lower symptom levels.